Effect of Packing Fraction on Shear Band Formation in a Granular Material Forced by a Penetrometer - Melo-Hurtado, F; Hamm-Hahn, L (2013)
Granular ensembles subjected to confinement forces can reach metastable states that often break down via formation of shear bands for sufficiently high deviatoric stress. In this article we investigate the flow induced in a granular ensemble that is perturbed by a vertically moving finger in a quasiplanar geometry. The flow exhibits spiral-like shear bands and evolves discontinuously in time, in concert with an oscillating penetration force. We characterize the nature of this nucleation-relaxation type process for loose to dense packing fractions. The nucleation dynamics is reasonably well described by a simple Mohr-Coulomb failure criterium in which the friction coefficient is a function of packing fraction. We contrast our findings with the recent work of Gravish. © 2013 American Physical Society.